The serving library annual 2017/18 : public fiction - Bertolotti-Bailey, Francesca; Bertolotti-Bailey, Stuart; Keefer, Angie; Mackler, Lauren; Reinfurt, David (Amsterdam : Roma Publications, 2017)
The Serving Library Annual' comprises a number of individual "Bulletins" organized around a theme for an international audience of designers, artists, writers, and researchers. Newly published by ROMA Publications in a yearly format, this inaugural issue is realised in collaboration with Public Fiction, a journal and exhibition-maker based in Los Angeles. It deals with acts of civil disobedience and other forms of resistance, particularly in view of the relationship between entertainment and power. Contributors include Hilton Als, Tauba Auerbach, Anne Carson, Mark Leckey, Adrian Piper, Frances Stark, and Martine Syms.
boek